Improving paediatric antimicrobial stewardship in hospital-based settings: why, where and how?. Issue 1 (13th March 2020) - Tanner, E; Munro, A P S; Gray, J; Green, H; Rutter, M; Jones, C E; Faust, S N; Alderton, M; Patel, S V
Abstract: Background: Antimicrobial resistance (AMR) is being recognized as a priority by healthcare organizations across the world. However, many children are managed on IV antimicrobials in hospital with very little consideration of antimicrobial stewardship issues. Objectives: A nurse-led paediatric ambulatory outpatient parenteral antimicrobial therapy (OPAT) service, managing children with common infections being ambulated on short courses of IV antimicrobials, was introduced within Southampton Children's Hospital in January 2018. We evaluated the impact of this service in terms of the quality of antimicrobial prescribing and timing of ambulation in children presenting with common infections. Methods: All cases managed within the service were reviewed in two separate 2 month time periods: prior to introduction of the service (September–October 2016) and then prospectively after its introduction (September–October 2018). Results: A total of 96% of IV antibiotic management decisions at 48 h were deemed appropriate in 2018, compared with 75% in 2016. A total of 64% of patients were ambulated on IV antibiotics at some point during their treatment course in 2018, compared with 19% in 2016. However, a significant proportion of antimicrobial decisions made at the point of presentation to hospital remained suboptimal in 2018. Conclusions: Children are commonly managed with IV antibiotics in hospital. We demonstrate marked improvements in appropriate antimicrobial use through the introduction of a nurse-led ambulatory OPAT service. In addition, such a service can promote a greater proportion of children being ambulated from hospital, freeing up valuable inpatient beds and potentially delivering cost savings that can be used to fund such services.